Reduction in Enteroccocus faecalis counts produced by three file systems in severely curved canals (Research, Society and Development, 2021)
Aim: This study evaluated the effectiveness of the mechanical reduction of intracanal bacteria produced by the endodontic systems Reciproc Blue (VDW GmbH), XP-Endo Shaper (FKG Dentaire) and ProTaper Next (Dentsply Sirona Endodontics) in severely curved canals by culture analysis. Methodology: Fifty severely curved mesiobuccal canals of mandibular molars were selected and instrumented. Following this, six specimens were selected as control, while 44 canals were contaminated with Enterococcus faecalis strains (ATCC 29212). Specimens were incubated for 21 days at 37 ºC. Then, contaminated specimens were randomly divided into 3 groups (n=14): ProTaper Next (G1), XP-Endo Shaper (G2) and Reciproc Blue (G3). Control Group: Six non-contaminated canals were prepared with one of the 3 file systems (n=2). Microbial samples were obtained before (S1) and after root canal preparation (S2). Two roots were observed using scanning electron microscopy to verify biofilm formation.  Quantitative culture analyses of intracanal E. faecalis reduction was performed using CFUs, and the Wilcoxon test was used for intragroup analysis, and intergroup analysis was performed using Kruskal-Wallis test. The level of significance for all analyses was set at P < .05. Results: All systems presented effective bacterial reduction (p